Truth stained lies - Blackstock, Terri, 1957- (Blackstock, Terri, 1957- Moonlighters series, 2012)
Three sisters--an investigative blogger, a cab driver, and a stay-at home mom--investigate to try and clear their brother's name after he is accused of murder.